Blood Glucose Fluctuations in Type 2 Diabetes Patients Treated with Multiple Daily Injections - Li, Feng-fei (Hindawi Publishing Corporation, 2016)
To compare blood glucose fluctuations in type 2 diabetes mellitus (T2DM) patients were treated using three procedures: insulin intensive therapy which is continuous subcutaneous insulin infusion (CSII), MDI3 (three injections daily), and MDI4 (four injections daily). T2DM patients were hospitalized and were randomly assigned to CSII, aspart 30-based MDI3, and glargine based MDI4. Treatments were maintained for 2-3 weeks after the glycaemic target was reached. After completing the baseline assessment, 6-day continuous glucose monitoring (CGM) was performed before and after completion of insulin treatment. Treatment with CSII provided a greater improvement of blood glucose fluctuations than MDI (MDI3 or MDI4) therapy either in newly diagnosed or in long-standing T2DM patients. In long-standing diabetes patients, the MDI4 treatment group had significantly greater improvement of mean amplitude glycemic excursion (MAGE) than the MDI3 treatment group. However, in patients with newly diagnosed diabetes, there were no significant differences in the improvement of MAGE between MDI3 and MDI4 groups. Glargine based MDI4 therapy provided better glucose fluctuations than aspart 30-based MDI3 therapy, especially in long-standing T2DM patients, if CSII therapy was not available.